Stratigraphic and volcanic signatures of Miaolingian-Late Ordovician rift pulses in the Alborz Mountains, northern Iran. (1st August 2022) - Álvaro, J. Javier; Ghobadi Pour, Mansoureh; Sánchez-García, Teresa; Kebria-ee Zadeh, Mohammad-Reza; Hairapetian, Vachik; Popov, Leonid E.
Graphical abstract: Highlights: The Cambrian-Ordovician succession of the eastern Alborz Mountain Range displays uplift episodes associated with erosion. The SPICE chemostratigraphic shift marks the Miaolingian–Furongian boundary. Alkaline to subalkaline magmatic activities are separated by quiescent intervals of up to 35 m.y. Intraplate (continental rift) volcanism reflects OIB-type mantle sources. Plume-related rift pulses are linked to a large igneous province about 600 km across. Abstract: Recent reconnaissance geological mapping, identification of unconformities and chronostratigraphic dating of Miaolingian to Ordovician strata in the eastern Alborz Mountains have led to recognition of synsedimentary uplift episodes associated with block tilting and partial erosion of the Cambrian Mila and Ordovician Simeh Kuh, Qumes and Lashkarak formations. A chronostratigraphic revision of the Miaolingian-Late Ordovician fossil content is presented, and the Steptoean Positive Carbon Isotope Excursion (SPICE) chemostratigraphic shift, marking the Miaolingian–Furongian boundary, is constrained close to the Members 2/3 contact of the Mila Formation. Upper Ordovician basaltic lava flows embedded in the Abarsaj Formation and Devonian sills and dykes intruded in the Mila and Simeh-Kuh formations were geochemically analysed and compared with the voluminous lava eruptions recognized in the Katian-Llandovery Soltan-Maidan and Gorgan Schists formations, and in the ?Emsian-Eifelian Mighan Formation. They represent successive magmatic pulses of alkaline to subalkaline activities, separated by background (quiescent) intervals of up to 35 m.y., characterizing an intraplate field (continental rift) affinity compatible with OIB-like (ΔNb greater than 0) mantle sources. Successive Miaolingian-Mid Ordovician (volcanic-free) uplift episodes were related to lithospheric doming preceding the onset of stepwise plume-related rift pulses, which shaped a large igneous province with transects of about 600 km, linking the Damghan and Alestan domains of the eastern Alborz Mountains with South Kopet-Dagh and some blocks of Central Iran.